2018
DOI: 10.11646/zootaxa.4378.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Key for identification of the parasitoids (Hymenoptera: Braconidae: Aphidiinae) of aphids infesting alfalfa in Europe

Abstract: Although Aphidiinae parasitoids have been used as agents for biocontrol of alfalfa aphids for more than half a century and have been the subject of numerous ecological investigations, there is an evident lack of systematic studies on the parasitoids of aphids infesting alfalfa in Europe. Here we present an original and up-dated key for identification of both native and invasive Aphidiinae parasitoids attacking aphids that feed on alfalfa in Europe. In total, 20 species are keyed and illustrated with scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…For the random collection samples, all infested twigs from one date and one field were pooled and treated as a single sample. Adult parasitoids and hyperparasitoids were preserved in 70% alcohol in microtubes (2 mL), and individuals were classified at the species level using taxonomic keys by Graham [22], Kamijo and Takada [23], Rakshani et al [24,25], Kavallieratos et al [26], and Ghaliow et al [27]. All samples belonging to the Encyrtidae family were sent to Dr John Noyes at the British Museum for further classification.…”
Section: Methodsmentioning
confidence: 99%
“…For the random collection samples, all infested twigs from one date and one field were pooled and treated as a single sample. Adult parasitoids and hyperparasitoids were preserved in 70% alcohol in microtubes (2 mL), and individuals were classified at the species level using taxonomic keys by Graham [22], Kamijo and Takada [23], Rakshani et al [24,25], Kavallieratos et al [26], and Ghaliow et al [27]. All samples belonging to the Encyrtidae family were sent to Dr John Noyes at the British Museum for further classification.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence (Ghaliow et al 2018) indicated that Aphidius banksae [former Aphidius staryi (Das & Chakrabarti 1990), synonymy by Kittel (2016)], which is described from Israel and Turkey, occurs in Europe and it is widely distributed from Greece to Great Britain. Aphidius colemani is a biological control agent distributed in Europe and the Mediterranean region.…”
Section: Discussionmentioning
confidence: 99%
“…In the last dozen years, there were 40 papers published in which the authors provided identification keys for Aphidiinae genera and species. The studies can be divided according to subject into several groups: (1) identification keys for Aphidiinae from specific (local) areas: from the Middle East and North Africa [86], Iran [33,86 and references therein], Malta [115], Argentina [116], Pakistan [117,118], Australia [78], Costa Rica [119], Serbia [69], and China [120]; (2) identification keys for species within tribes [120], subtribes [53], genera [16,42,44,47,[49][50][51][52]55,108,112,121], and species complexes [111]; and (3) identification keys for Aphidiinae species related to specific aphids [30], plants [32,36,[122][123][124][125][126][127], and habitats [128].…”
Section: Keys To Unlock An Easier Scientific Existencementioning
confidence: 99%